Pengaruh Profitabilitas, Struktur Modal, dan Good Corporate Governance terhadap Nilai Perusahaan Jasa Sektor Properti, Real Estate dan Konstruksi Bangunan Sub Sektor Properti dan Real Estate yang terdaftar di Bursa Efek Indonesia Tahun 2011-2015 - Elza Aldilla Anastasia; Yuni Utami (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2016)
Effect of Profitability, Capital Structure, and Good corporate governance on the Value of Service Companies in the Property, Real Estate and Building Construction of Property and Real Estate Sub-Sector Listed on the Indonesia Stock Exchange in 20112015. Essay. Tegal: Faculty of Economics, Pancasakti University Tegal 2017. The purpose of this study was to determine the effect of profitability, capit al structure and good corporate governance on the value of service companies in the property, real estate and building construction sectors property and real estate sub-sectors listed on the Indonesia Stock Exchange in 2011-2015. The hypothesis in this study is that it is assumed that profitability, capital structure and good corporate governance have an effect on the value of service companies in the property, real estate and building construction sectors, property and real estate sub-sectors listed on the Indonesia Stock Exchange in 2011-2015. The data collection method used in this study is documentation. While the data analysis method used is the classic assumption test, multiple regression, simultaneous test, partial test, and coefficient of determinati on analysis. From the results of the t-test calculation, the value of tcount is 3.663> t table of 1.98 with a significance value of 0.000 <0.05, meaning that there is a positive and significant effect on profitability on firm value. From the results of the t-test calculation, the value of tcount is 0.035 <ttable of 1.98 with a significance value of 0.972> 0.05, which means there is a positive and insignificant effect of the capital structure on firm value. From the results of the t-test calculation, the value of tcount is 1.829 <ttable of 1.98 with a significance value of 0.071> 0.05, which means there is a positive and insignificant effect of good corporate governance on firm value. Based on the results of the F test obtained Fcount of 5.573> Ftable of 2.68 with a significance value of 0.001 <0.05 means that there is a positive and significant effect of profitability, capital structure and good corporate governance on firm value.